DEVELOPMENT OF CREATIVE THINKING IN FUTURE TEACHERS (BASED ON THE CULTURE OF READING) - Yaxshilikova, Hilola Ulug‘bek qizi (Educational Research in Universal Sciences, 2023)
Creative thinking is a vital skill for teachers as it enables them to engage students, design innovative lesson plans, and adapt to ever-changing educational landscapes. One way to nurture creative thinking in future educators is by cultivating a strong reading culture. This article examines the significance of developing creative thinking skills in prospective teachers through fostering a culture of reading.